Optimization Of Time and Catalyst Mass of Polyethylene Terephthalate (PET) Microplastic Waste in Caranx Sp. Fish at Padang City by Glycolysis Method - Elvinda, Reza; Dewata, Indang (Periodic, 2019)
There is need to recycle Polyethylene Terephthalate (PET) waste, being one of the most widely used plastics in the industries and household. This material is usually used in beverage packaging, leading to increasing quantities reported every year, and recycling is needed because of poor automatic degradation ability. The phenomenon is estimated as dangerous to the terrestrial and aquatic environments. Furthermore, glycolysis method was performed using ethylene glycol (EG) solvent, at PET:EG ratio of 1:3, under constant temperature, and the reflux time was varied at 2.5, 3, 3.5, 4 and 4.5 hours. However, the catalyst mass used was varied at 0.04 g, 0.07 g, 0.1 g, 0.13 g and 0.16 g, to identify the optimal conditions. The best results were obtained at the temperature of 196oC, within 3.5 hours, with a catalyst mass of 0.1 g, and 93.409 % BHET yeild. This product was characterized using FTIR test to confirm the existence of important groups, and followed by application on fish samples in Padang City. The results obtained in the absence of white crystals in the determination results of microplastic waste in fish samples.